Opistognathus albicaudatus, a new species of jawfish (Teleostei: Opistognathidae) from the Andaman Islands - Smith-Vaniz, William F. (Zootaxa, 2011)
A new species of jawfish, Opistognathus albicaudatus, is described based on two specimens, 91.4–94.8 mm SL, from the Andaman Islands. The combination of an elongate upper jaw produced as thin flexible lamina, and a unique colour pattern consisting of an abruptly white caudal fin and gill arches with a series of 8–10 small dark spots, each near the base of a gill raker, distinguishes the new species from other congeners. Based on morphological similarity and general color pattern, the new species seems to be most closely related to Opistognathus variabilis.These two species appear to have allopatric distributions. A range extension for O. cyanospilotus is also reported.